Peran Komunikasi Efektif Dosen dalam Meningkatkan Efektivitas Penyelesaian Tugas Akhir Mahasiswa - Ircham Surahman; A. Zain Sarnoto; Shunhaji, Akhmad (Edukasiana: Journal of Islamic Education, 2024)
Abstract This research aims to explore and analyze the role of effective communication played by lecturers in the context of increasing the effectiveness of students' final assignment completion. Good communication between lecturers and students has a significant impact on understanding, motivation, and the final results of the final project. This research uses a qualitative approach with in-depth interviews with lecturers and students who are currently completing or have completed their final assignments. The results of this research indicate that effective lecturer communication can provide positive encouragement to students, increase understanding of final assignment requirements, and stimulate motivation to complete projects well. Factors such as the lecturer's time availability, listening ability, providing constructive feedback, and an adaptive pedagogical approach are key elements in achieving effective communication. The importance of supporting students through open and constructive communication and providing appropriate guidance at every stage of final assignment completion is also a key finding. This research contributes to further understanding of the relationship between lecturer communication and the effectiveness of students' final assignment completion, as well as providing valuable insights for higher education institutions to improve the quality of education and final assignment guidance.